The Potential Regulators of Amyloidogenic Pathway of APP Processing in Alzheimer’s Disease - Daria Krawczuk; Agnieszka Kulczyńska-Przybik; Barbara Mroczko (Biomedicines)
The amyloidogenic processing of amyloid precursor protein (APP) plays a pivotal role in the pathogenesis of Alzheimer’s disease (AD), primarily through the generation of amyloid-beta (Aβ) peptides, which aggregate to form toxic plaques in the brain. The regulation of amyloidogenic APP processing is a complex interplay of enzymes, proteins, and signaling pathways, all of which contribute to the development and progression of Alzheimer’s disease. Understanding the intricate mechanisms and molecular players involved in APP processing substantially enhances our knowledge of Alzheimer’s disease pathology and holds promise for the development of biomarkers of ongoing pathology at the earliest stages of Alzheimer’s disease. In this review, we aimed to investigate selected factors that regulate the amyloidogenic pathway of APP processing.